Field relations, petrography, and age of plutonic units in the Saint John area of southern New Brunswick - White, Chris; Barr, Sandra; Bevier, Mary; Deveau, Kevin (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1990)
Intrusive rocks in the Saint John area of southern New Brunswick are divided into separate plutonic units based on field relations and rock type. The oldest intrusive rocks are granodioritic orthogneisses in the Brookville Gneiss that have an igneous crystallization age of ca. 60S Ma, and a metamorphic age of ca. 564 Ma. The metamorphic age of the orthogneiss provides an approximate maximum age for post-metamorphic plutons that range in composition from gabbro to granite. One of these, the Rockwood Park Granodiorite, has a U-Pb age of 538 ± 1 Ma. On the basis of field relations, the Rockwood Park Granodiorite occupies an intermediate position in the intrusive sequence of plutons in the Saint John area. We therefore speculate that these plutons are mainly Cambrian rather than Precambrian as has been generally assumed.